2014
DOI: 10.1080/15226514.2013.876964
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes as Bioindicators of Ecosystem Recovery During Phytoremediation of Crude Oil Contaminated Soil

Abstract: Restoration of a weathered crude oil contaminated site undergoing phytoremediation was evaluated using nematodes as bioindicators. Samples were collected twice per year equating to spring and fall/winter. Mean annual total abundances ranged from 18-130 in the non-fertilized non-vegetated control (CTR) to 69-728 in tall fescue-ryegrass (FES) to 147-749 (100 g(-1)) in the fertilized bermudagrass-fescue (BER) treatment. Proportions of plant-parasitic (PP) and free-living (FL) nematodes were significantly impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…On the other hand, in the Slow phase, the peak of UCM shifted to the right, indicating that in the final phase of the treatment the shorter chains of hydrocarbons, produced in the Rapid phase, were degraded; furthermore, the residual most abundant fraction was characterized by a longer chain of HPH as compared to the fraction predominant at the beginning of the experiment. Finally, the chromatograms analysis proved that there was no significant difference between BS and BAS, confirming that even in terms of characteristics of hydrocarbon UCM, the two operating conditions were comparable Other studies also observed similar biodegradation pathways in landfarming systems: the rapid biodegradation of the lower weight hydrocarbons (with a shorter retention time in the chromatographic analysis) determined a progressive increase of the relative abundance of hydrocarbons having higher molecular weights (with a longer retention time) compared to the total content (Savin et al 2015;Wang et al 2016).…”
Section: Chromatograms Analysissupporting
confidence: 59%
“…On the other hand, in the Slow phase, the peak of UCM shifted to the right, indicating that in the final phase of the treatment the shorter chains of hydrocarbons, produced in the Rapid phase, were degraded; furthermore, the residual most abundant fraction was characterized by a longer chain of HPH as compared to the fraction predominant at the beginning of the experiment. Finally, the chromatograms analysis proved that there was no significant difference between BS and BAS, confirming that even in terms of characteristics of hydrocarbon UCM, the two operating conditions were comparable Other studies also observed similar biodegradation pathways in landfarming systems: the rapid biodegradation of the lower weight hydrocarbons (with a shorter retention time in the chromatographic analysis) determined a progressive increase of the relative abundance of hydrocarbons having higher molecular weights (with a longer retention time) compared to the total content (Savin et al 2015;Wang et al 2016).…”
Section: Chromatograms Analysissupporting
confidence: 59%
“…Crude oil pollution actively influences soil nematodes community composition resulting in the negative correlation of trophic diversity and genus number with the duration of petroleum exploration in oil fields (Wang et al, 2009). Savin et al (2015) in agreement, stated that crude oil pollution has long term negative effects on the faunal composition of the soil ecosystem. However, Dechang et al (2011) observed that ecosystem instability common in crude oil impacted soils was due to pollution induced low trophic diversity of resident basal organisms such as soil nematodes.…”
Section: Introductionmentioning
confidence: 89%